KONSEPSI HADIS MUKHTALIF DAN METODE PENYELESAIANNYA DI KALANGAN ULAMA FIQH - Muhammad Amil Hikam Assaaf; Putri Kurnia Putri Kurnia Febriyanti (El-Furqania : Jurnal Ushuluddin dan Ilmu-Ilmu Keislaman, 2023)
This article contains the concept of mukhtalif hadith and its method of completion among fiqh scholars. Among the sunnah that is quite difficult to understand is the sunnah or hadith that are contradictory or mukhtalif. For ordinary people who do not have the power of faith will have negative thoughts and maybe accusations against the sunnah of the prophet Muhammad SAW. Therefore, the scholars of hadith do not remain silent on these accusations. Likewise Fiqh Ulama, the approach of Fiqh Ulama in completing collaborative hadiths is no different from what is done by Hadith Ulama. However, the scholars of hadith generally refer to the aspects of the hadith of the Prophet as role models. While the scholars of fiqh are more important in the interests of the law. In addition, hadith scholars are more likely to understand the Prophet's hadith textually, while fiqh scholars tend to understand contextually in order to take the legal basis.